PENGARUH GREEN MARKETING TERHADAP MINAT BELI KONSUMEN PADA PRODUK ECOBAG DI INDOMARET (STUDI PADA INDOMARET TERUSAN BUAH BATU KOTA BANDUNG) - fikriansyah, Akmal (PT Naureen Digital Education, 2024)
**Translation:** Due to the increasing use of plastics every day, the amount of plastic waste is causing global warming. Society is beginning to realize that the products they use can lead to an increase in waste. Some customers are becoming more selective when purchasing goods. Companies that consider environmental issues in their production operations have created a new phenomenon in the marketing industry, known as eco-friendly marketing strategies. The aim of this study is to determine the influence of green advertising on purchase intention. Using a questionnaire as the data source, this research is quantitative in nature. Consumers who purchase ecobag products at Indomaret are the subjects of this study. A purposive sampling method was used to determine a sample of one hundred individuals. The results of the study indicate that green marketing significantly increases purchase intention with a value above 0.492, meaning that 49.2% of the influence of green marketing on the purchase intention of ecobags, and the remaining 50.8% is caused by other factors.